2021
DOI: 10.33448/rsd-v10i2.12813
|View full text |Cite
|
Sign up to set email alerts
|

Blood glucose and outcomes in critically ill children in Brazilian Amazon: an observational study

Abstract: Objectives: To determine blood glucose distribution values; to assess the association of admission serum glucose levels with 28-day mortality to the frequency of invasive mechanical ventilation-free days. Design: Retrospective cohort studySetting: Brazilian Amazon Region. Patients: Population (n = 400) composed of patients admitted to the pediatric intensive care unit, from January 2016 to December 2017. Exclusion criteria were patients with length of stay of <24 hours; diabetes mellitus; suspicion or evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 27 publications
0
0
0
Order By: Relevance
“…Also, non-survivors had a higher percentage of inotropic support (87.8%) with a statistical significance, which is in accordance with the following studies: Tirkey and Verma 33 and de Farias et al 17 However, we found no statistical difference between living and deceased patients regarding gender or the presence of any system affection.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Also, non-survivors had a higher percentage of inotropic support (87.8%) with a statistical significance, which is in accordance with the following studies: Tirkey and Verma 33 and de Farias et al 17 However, we found no statistical difference between living and deceased patients regarding gender or the presence of any system affection.…”
Section: Discussionsupporting
confidence: 92%
“…This study demonstrated that non-survivors had shorter PICU stay, with a median of 2 (IQR 1–6) days, which may be the cause of their shorter stay and subsequent mortality. On the other hand, another study by de Farias et al 17 revealed that PICU stay did not significantly affect the outcome, with a p -value of 0.08.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation